2019
DOI: 10.3390/app9050895
|View full text |Cite
|
Sign up to set email alerts
|

Feature Adaptive and Cyclic Dynamic Learning Based on Infinite Term Memory Extreme Learning Machine

Abstract: Online learning is the capability of a machine-learning model to update knowledge without retraining the system when new, labeled data becomes available. Good online learning performance can be achieved through the ability to handle changing features and preserve existing knowledge for future use. This can occur in different real world applications such as Wi-Fi localization and intrusion detection. In this study, we generated a cyclic dynamic generator (CDG), which we used to convert an existing dataset into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The confusion matrix is used to campout the classification accuracy of the MLP1 model, as illustrated in Figure 5. The MLP1 model achieves the best accuracy of 95.62% using (1) [25][26][27][28][29][30][31] after 100 epochs.…”
Section: Simulation Evaluation and Resultsmentioning
confidence: 99%
“…The confusion matrix is used to campout the classification accuracy of the MLP1 model, as illustrated in Figure 5. The MLP1 model achieves the best accuracy of 95.62% using (1) [25][26][27][28][29][30][31] after 100 epochs.…”
Section: Simulation Evaluation and Resultsmentioning
confidence: 99%
“…The reason is that the testing captures the accuracy of predicting the location of the testing dataset which is composed of different records, however, it does not include an actual records generated from a traversed scenario. In order to test the algorithm based on given scenarios we adopt the simulator that is presented in [24]. This simulator allows providing a whole trajectory and it generates its corresponding time series of records from the dataset.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the authors applied the concept to Wi-Fi navigation and showed good performance improvement in the context of feature adaptability of Wi-Fi positioning system to preserve the knowledge in its neural network. The work conducted in [24,25] describes a novel type of extreme learning machine, using external memory and transfer learning; ITM-OSELM. In this study, the authors applied the concept to Wi-Fi localization and showed good performance improvement in the context of cyclic dynamic and feature adaptability of Wi-Fi navigation.…”
Section: Related Workmentioning
confidence: 99%
“…This method calculates the time to process large amounts of data; however, setting a baseline that can be effectively distinguished is difficult. Al-Khaleefa et al [17] simulated the operation of the human brain, trained the weights of intermediate nodes with infinite term memory, and classified the packets into normal or abnormal patterns. This method is complex and time-consuming; security administrators cannot obtain clear information of the attacks through the trained weightings of nodes.…”
Section: Literature Reviewmentioning
confidence: 99%